Analisis Implementasi Kebijakan Penggunaan Antibiotika Rasional Untuk Mencegah Resistensi Antibiotika di RSUP Sanglah Denpasar: Studi Kasus Infeksi Methicillin Resistant Staphylococcus Aureus - Negara, Ketut Surya (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2014)
Irrational use of antibiotics lead to antibiotic resistance. Implementation of the policy on the use of antibiotics in Sanglah Hospital in Denpasar has never been evaluated. The purpose of this study to know the implementation of policy on the use of antibiotics, preventing antibiotics resistance and determine the application ofthe WHO interventions to improve rational drug use. This research is aqualitative descriptive study, with interviews and document traces. Data analysis through content analysis. The result shows the implementation of antibitics usage policy and application of WHO intervention has not gone well. Prevention of antibiotic resistance have not been well coordinated by team of four pillars of Antimicrobial Resistance Control Program. Required revision and dissemination of antibiotic usage policy traces, as well as prevention and control of infection.